2020
DOI: 10.1002/ams2.557
|View full text |Cite
|
Sign up to set email alerts
|

Activities of daily living status and psychiatric symptoms after discharge from an intensive care unit: a single‐center 12‐month longitudinal prospective study

Abstract: Aim In post‐intensive care syndrome (PICS), long‐term survivors of critical illness present various physical and mental symptoms that can persist for years after discharge. Post‐intensive care syndrome in Japan has not been well described, so this study aims to elucidate its epidemiology. Methods We undertook a single‐center prospective longitudinal cohort study in a mixed intensive care unit (ICU) in a Japanese tertiary hospital. Adult patients emergently admitted to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(48 citation statements)
references
References 34 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…This may have contributed to our findings. Additionally, this difference in populations could also have contributed to the higher prevalence of PTSD in a recent Japanese ICU study, which analyzed only emergency-admitted patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have contributed to our findings. Additionally, this difference in populations could also have contributed to the higher prevalence of PTSD in a recent Japanese ICU study, which analyzed only emergency-admitted patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wu and colleagues [ 9 ] evaluated the prevalence of mental health issues in post-ICU patients in Hong Kong. In Japan, in a recent single-center cohort study, Shima and colleagues [ 10 ] found that 3 and 12 months after ICU discharge, over half of the Japanese patients admitted to the emergency unit experienced impaired activities of daily living and/or psychiatric symptoms. They reported that the prevalence of PTSD was 20% at 12 months post-ICU discharge.…”
Section: Introductionmentioning
confidence: 99%
“…We also evaluated BI scores before ICU admission (baseline) from information gained from patients’ proxies. The main results of the W-PICS study have been previously reported elsewhere [ 3 ]. The present sub-analysis includes all patients (no missing data) of BI both before ICU admission and three months after ICU discharge, and who can be evaluated to ascertain whether there was worsened ADL status between before and after their admission to ICU.…”
Section: Methodsmentioning
confidence: 99%
“…Physical and cognitive impairment often leads to functional disability, such as adversely affected activity of daily living (ADL) status. Approximately 30% of survivors from critical illness were reported to have reduced ADL status [ 2 , 3 ]. Early prediction of impairment of ADL status after intensive care unit (ICU) discharge may facilitate the implementation of preventive measures and help patients and their families better anticipate the post-ICU course.…”
Section: Introductionmentioning
confidence: 99%
“…This is a sub‐analysis of Wakayama post‐intensive care syndrome (W‐PICS) study, a single center prospective longitudinal study. 14 W‐PICS‐study was approved by the Wakayama Medical University Ethics Committee (approval no. 1864), and was registered to the UMIN Clinical Trial Registry, UMIN000023743 (Registered on September 1, 2016, https://upload.umin.ac.jp/cgi‐open‐bin/ctr_e/ctr_view.cgi?recptno=R000027346 ).…”
Section: Methodsmentioning
confidence: 99%